Fertilizacion de viveros de palma africana (Elaeis guineensis jacq), variedad cirad, con cenizas de maderas rollizas mas fertilizacion quimica - Yanchapaxi Lopez, Juan Luis (2011)
This proposal was made in km. 40 of the route Santo Domingo - Quinindé, near the flower municipality of Valle in the Treasury of the Cedeño Ruiz brothers, located in the North latitude 00 ° 01 "and in the 79th 22" in length. The length of the proposal was for six months in field work and main objective was to "Establish the efficacy of fleshier wood ashes using more chemical fertilization complement in the management of African Palm, variety CIRAD nurseries". The specific objectives were to: assess the agronomic behaviour of the Palm under the study treatment. Determine the optimal percentage of ash used in three treatments and establish the cost-effectiveness of treatments in study. Treatments through experimental design DCA settled through percentages of cocoa with texture Orchard land use franco - sandy and the percentage of fleshier wood ashes were: T1 = 100% cocoa with texture Orchard land - Frank sandy, witness. T2 = 90% cocoa texture free huerta land Sandy more 10% ash.